PENGARUH MOTIVASI, LINGKUNGAN KERJA, DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PADA SEKRETARIAT DEWAN KOTA SEMARANG - Reza Intan Permatasari, 13.05.51.0020; Indriyaningrum, Kis (Students' Journal of Economic and Management, 2018)
Abstract This study aims to analyze the influence of Motivation, Leadership and Work Environment on Employee PerformanceSecretariat Dewan Semarang City. The population in this study is the total number of employees amounted to 83 respondents. The data used are primary data, that is data obtained directly from the source. The technique for data collection is done by means of questionnaires.The analysis method used is data feasibility test, model feasibility test, hypothesis with used multiple linear regression The research results show that motivation has a positive and significant impact on the performance of Secretariat Dewan Semarang City.Work has a positive and significant impact on the performance of Secretariat Dewan Semarang City.Motivation has a positive and significant impact on the performance of Secretariat Dewan Semarang City.Keywords: Motivation, Workplace Environment, Competence and Employee Performance.